Simulation of electromagnetic field propagation generated by radio waves from antennas for mobile cellular communications - Stankevičius, Žilvinas (Geodesy and Cartography, 2012)
The methods frequently employed for predicting the intensity of an electromagnetic field in urban localities are based on empirically established factors. In order to predict the intensity of the electromagnetic field in an adjacent transmitter zone and on building facade flats, the method of simulating of direct visibility rays seems to be a suitable tool. With reference to the introduced method, the article describes the offered algorithm applied for performing experimental calculations. Also, the method of monitoring has been based on the calculated values of the intensity of the electromagnetic field.